(untitled) (Development Service Industry Management, 2024)
The article discusses the evolutionary nature of financial thinking and its impact on modern economic life. It takes place in a social and natural environment that changes and thereby changes the data of economic activity; this fact is important, and these changes (wars, revolutions, etc.) often lead to industrial changes, but they are not their primary causes. The essence and understanding of financial thinking and accounting is presented, emphasising the importance of concentrating on the scale of the economy. A comprehensive approach to the instruments that do not take into account the rich ‘biodiversity’ that characterises the financial world, the world of financial accounting, they also ignore the role of natural selection. A conclusion is made on the identification of common features that are inherent in the modern financial world and the true evolutionary system of economic life.